(untitled) (Iraqi Journal of Medical Sciences, 2009)
Background: Platelets play an important role in the development of intravascular thrombosis, the major cause of acute coronary syndromes. Platelet size has been considered to reflect platelet activity. Objectives: The aim of this study is to investigate the clinical value of platelet volume indices (PVI) in the spectrum of ischemic heart diseases and the possibility of being a risk factor for acute myocardial infarction (MI). Patients &Methods: Thirty six (36) patients were included in the study: 22 of them have myocardial infarction (MI) and 14 have unstable angina (UA). Risk factors and history of stable angina (SA) were reviewed and studied by Chi square. Complete blood count and platelet volume indices (PVI): mean platelet volume (MPV), platelet large cell ratio (P-LCR), and platelet distribution width (PDW) were done using automated hematology analysis system and studied by t-test and correlation analysis. All P values were two sided and P value of < 0.05 was considered statistically significant. Results: It is found that MPV and P-LCR were the most significant parameters that showed statistical difference between patient with UA and those with MI (P=0.042 & P=0.031) respectively unlike other parameters (platelets count or PDW) (P=0.703 & P=0.094). There were no correlations between MPV & other platelet indices with existing past history of SA as well as other risk factors for acute coronary syndrome (P=0.811). Conclusion: Because it is simple, economic, and practical, MPV and P-LCR can be used in predicting the possibility of acute thrombosis in patients with coronary artery diseases. Key words: Platelets, platelet volume indices, atherosclerosis, myocardial infarction, unstable angina, coronary artery disease.